Odpowiedzi

2009-11-05T19:57:22+01:00
A). (y + 1) ²= y²+2y+1
b). (2x + 4) ²= 4x²+16x+16
c). (3 + 2x) ²=9+12x+4x²
d). (x² + 1) ²= x⁴+2x²+1
e). (2a + 5b) ²= 4a²+20ab+25b²
f). (3xy + 1) ²= 9x²y²+6xy+1
g). (√3 + 1) ²=3+2√3+1=4+2√3
h). (1 + √2) ²=1+2√2+2=3+2√2
i). (√3 + √12) ²=3+2razy pierwiastek z 36+12=3+12+12=27
15 4 15
2009-11-05T20:01:14+01:00
(y+1)²=y²1²=y²+1
(2x+4)²=4x²+16
=9+4x²
=x(do potęgi4)+1
=4a²+25x²
=9(xy)²+1
=3+1=4
=1+2=3
=3+12=15
chyba dobrze
5 4 5
2009-11-05T20:11:48+01:00
A)4y+1
b)20x+16
c)9+12x+4x4²
d)x⁴+2x²+2x²+2
e)4a²+10ab+10ab+25b²
f)6x²y²+3xy+3xy+2
g)3+√3+√3+2
h)2+√2+√2+2
i)3+4√3+4√3+12
2 2 2